Stratum lacunosum-moleculare interneurons of hippocampal CA1 region. II. Intrasomatic and intradendritic recordings of local circuit synaptic interactions - Lacaille, JC (J Neurosci, 1988)
Simultaneous intracellular recordings were obtained from stratum lacunosum-moleculare (L-M) interneurons and CA1 cells, and their local circuit synaptic interactions were examined. Synaptic interactions with pyramidal cells were evaluated in both intrasomatic and intradendritic pyramidal cell recordings. Stimulation of L-M interneurons evoked small- amplitude IPSPs in 21% of intrasomatic (9/42 cell pairs) and in 26% of intradendritic (11/43) pyramidal cell recordings. The IPSP mean peak amplitude was 0.91 mV for intrasomatic and 0.67 mV for intradendritic recordings. IPSPs had slow onset and decay (approximately 80–90 msec), decreased in amplitude with membrane hyperpolarization, and were not associated with any apparent change in input resistance. No physiologic evidence of synaptic connections was found from pyramidal cells to L-M interneurons. Inhibitory synaptic interactions were also seen between L- M interneurons and stratum pyramidale interneurons (2 of 4 cell pairs). The IPSPs recorded in pyramidale interneurons were similar to the IPSPs recorded in pyramidal cells. During simultaneous recordings, L-M interneurons were activated at a shorter latency, i.e., in a feedforward manner with respect to pyramidal cells. Thus, L-M interneurons may mediate feedforward inhibition of CA1 pyramidal cells. The L-M interneuron-evoked IPSPs in pyramidal cells share some characteristics of the late IPSP recorded in CA1 pyramidal cells and may therefore contribute to this component of the IPSP.